Endobronchial Leiomyoma: A case report with cryoprobe extraction and review of literature. (2021) - Bawaadam, Hasnain; Ivanick, Nathaniel; AlShelli, Ihab; Krishna, Ganesh
Abstract: Large airway tumors are uncommon, accounting for about 0.6% of all pulmonary tumors [1–3 ]. The majority of these tumors (80–90%) are malignant, represented primarily by squamous cell carcinoma and adenoid cystic carcinoma [2, 4 ]. Benign central airway tumors are less common and are generally comprised of hamartomas and papillomas. Tracheobronchial leiomyomas are exceedingly rare, representing only about 0.6% of all benign lung neoplasms [3 ]. We report here on a case of primary endobronchial leiomyoma without uterine involvement treated successfully with cryoresection with excellent outcome.